2012
DOI: 10.1097/mpg.0b013e318253f2f0
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients Postcolectomy for Pediatric‐onset Ulcerative Colitis

Abstract: Background Ulcerative colitis in children can have a negative impact on quality of life (QOL). Methods We included 16 of 31 patients who underwent colectomy for ulcerative colitis before 20 years of age between 1980-2005 at UCSF Benioff Children’s Hospital. A disease-specific QOL questionnaire (IBDQ-32), validated for adults, was used to determine QOL and an additional questionnaire addressing bowel function and reproductive health in long term follow up of these patients. Results Median age at the time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In 2002, Loonen et al[ 23 ] concluded that adolescents have impaired QOL scores compared to younger children, whereas Gallo et al[ 18 ] found no association. An interesting study published by Deepal et al[ 24 ] in 2012, supported that post-colectomy QOL in UC patients was better when the diagnosis was made under the age of twelve. A possible interpretation of our result is that, as children grow into adolescence, they may be able to develop more efficient coping mechanisms and therefore be less vulnerable to the psychological effect of a chronic disease.…”
Section: Discussionmentioning
confidence: 98%
“…In 2002, Loonen et al[ 23 ] concluded that adolescents have impaired QOL scores compared to younger children, whereas Gallo et al[ 18 ] found no association. An interesting study published by Deepal et al[ 24 ] in 2012, supported that post-colectomy QOL in UC patients was better when the diagnosis was made under the age of twelve. A possible interpretation of our result is that, as children grow into adolescence, they may be able to develop more efficient coping mechanisms and therefore be less vulnerable to the psychological effect of a chronic disease.…”
Section: Discussionmentioning
confidence: 98%
“…However, it must be noted that these patients suffer greatly from stresses caused by their stoma. Patients have reported decreased sexual activity and fertility at the time of survey due to colectomy, especially for females [2], and occasionally prepared for death rather than accepted their condition and potential cure [3]. To avoid colostomies, various anal reconstructions have been performed and many alternative therapies have been examined and developed [46]; however, no alternative options have been able to solve this critical issue until now.…”
Section: Introductionmentioning
confidence: 99%
“…This is not the case with CD as it can appear in any part of the GIT. A colectomy will initially result in an ileostomy which can be difficult socially for the child, especially during puberty and the teenage years; however, it can be a rapid way to eliminate symptoms and get the child back to a normal life pattern.…”
Section: Regional Gastrointestinal Diseasesmentioning
confidence: 99%